Storage optimization for digital Quran using sparse matrix with hexadecimal representation - Omoush, Ashraf; Md Norwawi, Norita; Ismail, Roesnita; Abdul Wahid, Fauziah; Mazlan, Ahmad Akmaluddin (2017)
Digital Quran is a common application today in smart devices such as hand phones and tablet. The verses are usually presented using images of verses on written in an Arabic font.This raise issues related to storage when representing the whole Quran text.This study proposed a hexadecimal digital representation technique for words in Arabic using UTF-8 for character encoding which is backward compatible with ASCII code.This paper will explain three approaches used in representing the digital Quran.They are the hexadecimal representation for each Quranic words, sparse matrix in representing verses of Al-Quran and double offset indexing for transforming the sparse matrix to efficiently use the space. This representation proof more than 50% reduction in the memory space for storage thus will increase the searching speed.The storage of words being optimized through the use of one memory space for that particular word rather than one memory space for each Arabic character in the words .This technique helps optimized memory management for the whole digital Quran.Due to the smaller size, the digital Quran can be conveniently installed in the future as standard applications in mobile devices.